Pencegahan Stunting Melalui Pengoptimalan Kearifan Lokal Tanaman Bergizi Tinggi Dan Pijat Tui Na - Ratna Wijayatri; Eka Sakti Wahyuningtyas; Riza Nur Afifah; Tisa Fitria; Saniya Puspa Fasya; Kurnia Uji Hartati; Ermawati Ermawati (STMIK Royal, 2023)
Abstract: Barongan Hamlet is part of Donorojo Village, Tegalrejo District, Magelang Regency. In October 2022, Barongan Hamlet is in the top position for the number of stunting cases in the Donorojo Village area. The number of cases of stunting was recorded in 8 children out of 15 children aged < 5 years. In addition, there were 2 pregnant women, one of whom was detected as having KEK (chronic energy deficiency), so that they have the potential to give birth to stunted babies. One of the factors causing stunting is the lack of knowledge about nutrition during pregnancy and toddlerhood. Seeing the potential and natural resources of the Barongan area which is a rural area, the PPMT Team has a program to optimize the potential for local wisdom of family medicinal plants (toga), especially highly nutritious plants and baby/toddler massage. This activity was carried out using educational methods for cadres, youth, pregnant women and mothers of toddlers in Barongan Hamlet about risk factors, causal factors, prevention and management of stunting in the community. PPMT Team will train cadres, pregnant women and mothers of toddlers in utilizing highly nutritious plants that are easily found in the surrounding environment and doing Tui Na massage for toddlers. This activity is expected to support the resolution of stunting cases and prevent the emergence of new stunting cases. The results of the education and training activities carried out are an increase in knowledge about stunting, an increase in skills in empowering highly nutritious plants as a menu variation for toddlers, and skills in practicing Tui Na massage for toddlers.Keywords: Stunting; Toga; Tui Na massageAbstrak: Dusun Barongan merupakan bagian dari Desa Donorojo, Kecamatan Tegalrejo, Kabupaten Magelang. Pada Oktober 2022, Dusun Barongan berada pada posisi teratas jumlah kasus stunting di wilayah Desa Donorojo. Jumlah kasus stunting tercatat 8 anak dari 15 anak usia < 5 tahun. Selain itu, terdapat 2 ibu hamil yang salah satunya terdeteksi mengalami KEK (kekurangan energi kronis), sehingga berpotensi melahirkan bayi stunting. Salah satu faktor penyebab stunting adalah kurangnya pengetahuan tentang pemenuhan nutrisi di masa kehamilan dan masa balita. Melihat potensi dan sumber daya alam wilayah Barongan yang merupakan wilayah pedesaan, Tim PPMT memiliki program untuk mengoptimalkan potensi kearifan lokal tanaman obat keluarga (toga) khususnya tanaman bergizi tinggi serta pijat bayi/balita. Kegiatan ini dilaksanakan dengan metode edukasi bagi kader, remaja, serta ibu hamil dan ibu balita di Dusun Barongan tentang faktor risiko, faktor penyebab, upaya pencegahan dan tatalaksana stunting di masyarakat. Kemudian, Tim PPMT akan melatih kader, ibu hamil dan ibu balita di Dusun Barongan dalam mendayagunakan tanaman bergizi tinggi yang mudah ditemukan di lingkungan sekitar dan melakukan pijat Tui Na untuk balita. Hasil dari kegiatan edukasi dan pelatihan yang dilaksanakan adalah peningkatan pengetahuan tentang stunting, dan mendukung penuntasan kasus stunting, pencegahan munculnya kasus stunting yang baru peningkatan ketrampilan dalam pemberdayaan tanaman bergizi tinggi sebagai variasi menu bagi balita dan ketrampilan melakukan pijat Tui Na untuk balita.Kata kunci: Pijat Tui Na; Stunting; Toga